2017
DOI: 10.1371/journal.pone.0172114
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in prospective memory and their clinical correlates at 1-year follow-up in first-episode schizophrenia

Abstract: This study aimed to investigate prospective memory (PM) and the association with clinical factors at 1-year follow-up in first-episode schizophrenia (FES). Thirty-two FES patients recruited from a university-affiliated psychiatric hospital in Beijing and 17 healthy community controls (HCs) were included. Time- and event-based PM (TBPM and EBPM) performances were measured with the Chinese version of the Cambridge Prospective Memory Test (C-CAMPROMPT) at baseline and at one-year follow-up. A number of other neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 68 publications
2
17
0
Order By: Relevance
“…Consistent with Cheung et al () and Zhou et al ()'s earlier studies, our findings suggest that the 2 pm types have different trajectories, with time‐based PM improving initially and then plateauing, whereas event‐based PM slowly but progressively improves. We propose several possible reasons for the different trajectories.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Consistent with Cheung et al () and Zhou et al ()'s earlier studies, our findings suggest that the 2 pm types have different trajectories, with time‐based PM improving initially and then plateauing, whereas event‐based PM slowly but progressively improves. We propose several possible reasons for the different trajectories.…”
Section: Discussionsupporting
confidence: 91%
“…Findings of previous familial studies are inconsistent, with two studies (Wang et al, ; Zhou et al, ) suggesting familial association of PM impairments, but one (Lui et al, ) reporting negative results. On the other hand, previous longitudinal studies (Cheung et al, ; Zhou et al, ) have consistently suggested that time‐based PM is more temporally stable than event‐based PM, even when practice effect was controlled for, using parallel assessments of PM in the control group (Zhou et al, ). Compared with previous studies (Cheung et al, ; Zhou et al, ), our investigation has a longer follow‐up period and more sequential assessments.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations